ANALYSIS OF AGED CABLES` INSULATION WITH X-RAY FLUORESCENCE SPECTROMETRY - Friškovec, Nejc; Obreza, Manja; Pirc, Marko; Sredenšek, Klemen; Praunseis, Zdravko (Journal of Energy Technology, 2025)
The paper provides an analysis with X-ray fluorescence spectrometry of aged cable samples. The work encompasses a review of the electrical, mechanical and chemical properties, as well as measurement methods for determining those parameters. The analyses are based on physical principles that allow us to assess the condition of the cable insulation. Using the physical properties and measurement results, mathematical models can be formulated to describe the ageing of individual materials in the presence of specific influences. The goal of the paper is to establish the foundation for the development of a measurement method using X-ray spectral analysis. The methodology assumes that the presence of specific elements decreases or increases on the material’s surface as it ages. By using a standard indenter modulus test, we can determine reference points for X-ray spectral analysis. Sampling these points on differently degraded cables enables the establishment of criteria for acceptable cable insulation.